Distance Education and Academic Achievement in Business Administration: The case of the University of Akureyri - Edvardsson, Ingi Runar; Oskarsson, Gudmundur Kristjan (International Review of Research in Open and Distributed Learning, 2008)
This paper first presents the development of distance education in Icelandic universities. Its second aim is to present a detailed analysis of the distance education practice at the University of Akureyri (UNAK), Iceland. Finally, the paper aims at analysing academic achievement, as well as attitudes towards courses, among campus and distance students in business administration at UNAK. The research is based on secondary data from the university’s information system and official statistics. The findings reveal that distance education has increased significantly in Iceland in recent years. UNAK has had a leading role in developing distance education at university level in Iceland. Nearly half the students at UNAK are enrolled in distance education. Females take longer to finish their study than males, but they receive higher grades than males. Distance students take up to a year longer to finish their BSc programme than campus students. The study also has shown that distance students tend to receive lower grades in business administration at UNAK, and they are older, on average, than local students. Finally, both groups of students seem to express similar attitudes towards taught courses within the faculty. More research is needed in order to fully understand the factors behind the different achievements of distance and campus students.